Decentralized Production Circulation and Arrangement in Supply Chain Using Smart Operatives - Dhamija, Aruna (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Under the assumptions of complete sharing of information between organizational departments and the presence of an independent decision making authority for the entire supply chain, previous supply chain research highlights centrally controlled models. Due to information privacy, most of the facilities in the supply chain are functionally centralized in exercise. Collaboration between these functional units is most important for responding to rapid changes in customer requirements and for resolving conflicts. Intelligent Agent Systems have been shown to be effective in achieving collaboration and effective communication in the environment of distributed decision making. In this paper, intelligent agents are proposed and validated Reducing cost of a decentralized distribution planning process for development for multiple echelons, multiple products and multiple intervals.